THE EFFECT OF HEALTH PROMOTION ABOUT DISASTER MANAGEMENT TOWARDS THE LEVEL OF KNOWLEDGE OF YOUTH RED CROSS MEMBERS - Loren Juksen; Ida Rahmawati; Qrestha Utami (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2019)
Background: The potential for natural disasters in Bengkulu is very worrying. Mukomuko is one of the districts in Bengkulu Province which has a geographical location prone to earthquakes and Tsunami. Preparedness and disaster mitigation in school students is still low. Members of the youth red cross in senior high schools have never been exposed to disaster management.Objectives: The aim of this study was to determine health promotion to increasing knowledge about disaster management on students of youth red cross members.Methods: This study used pre and posttest without control group design. Population in this study were all students of youth red cross members at SMA Negeri 1 Mukomuko Bengkulu with the amount of 30 people. Sampling technique in this study used total sampling obtained samples were 30 people. Collecting data in this study used primary data obtained from SMA Negeri 1 Mukomuko and secondary data with filled out questionnaire.Results: The results of this study showed: (1) from 30 people there were 13 people (43,3%) before treatment were good knowledge, 16 people (53,3%) before treatment were moderate knowledge, and 1 people (3,3%) before treatment were low knowledge; (2) from 30 people there were 18 people (60%) after treatment were good knowledge and 12 people (40%) after treatment were moderate knowledge; (3) results of Paired Sample t-test obtained value of t = 3,023 with p-value = 0,005<0,05 significant means there was significant differences between knowledge about Disaster Management on Students before treatment and knowledge about Disaster Management on Students after treatment.Conclusion: The importance of direct information from health workers regarding disaster management has a continuing impact to be applied by youth red cross students when a disaster occurs. Key words: Health Promotion, Knowledge, Disaster Management.